Subsidence model of the ancient Alexandria Royal port linked to sea-level rise and natural hazards using integrated geophysical methods - Amr Z. Hamouda; Suzan M. El-Gharabawy; Ahmed Fekry; Mohamed A. Nassar; Mahmoud Salah (Egyptian Journal of Aquatic Research, 2021)
Marine geophysical methods are quite valuable in geoarchaeological investigations and remote seabed classifications due to their capability to cover vast areas in a short time and reveal fine details of the seafloor and subsurface features in unexcavated sites. The present study aimed to reconstruct the depositional history of the uppermost sediment sequence of the ancient Royal port of Alexandria during different historical periods, and point out the impact of the post-glacial eustatic sea-level rises and natural hazards that took place through the last 2000 years. To resolve this riddle, seismic and geomorphologic surveys were conducted by using a sub-bottom profiler and side scan sonar respectively in integration with previous sediment core data, to extrapolate the vertical extent of the strata and monitor the recent seafloor situation. The results of this study confirmed the subsidence of the ancient port mainly as a result of sea-level rises and the 365 AD tsunami. Seismic interpretations suggested a depositional scenario through successive stages from the Royal port’s construction until its abandonment, also the detailed analyses of backscatter images showed significant variations on the seafloor geomorphology that took place through the recent years which in turns give prominence to the impact of the short-term winds and storms as well.